Animatrix - Wachowski, Andy, 1967-; Wachowski, Larry, 1965-; Warner Home Video (Firm); Village Roadshow Pictures; NPV Entertainment (Firm) ([United States], 2003)
A collection of nine short animated films set in the world of The Matrix. Written by the creators of The Matrix and featuring animation by the creators of Cowboy Bebop, Aeon Flux, and Vampire Hunter D.
Final flight of the Osiris / written by Andy and Larry Wachowski -- Second renaissance, part I / written by Andy and Larry Wachowski -- Second renaissance, part II / written by Andy and Larry Wachowski -- Kid's story / written by Andy and Larry Wachowski -- Program / written and directed by Yoshiaki Kawajiri -- World record / written by Yoshiaki Kawajiri -- Beyond / written and directed by Koji Morimoto -- Detective story / written and directed by Shinichiro Watanabe -- Matriculated / written and directed by Peter Chung
Title from title screen
DVD format
English or Japanese dialogue ; English, Japanese, Chinese, Thai Korean or Bahasa subtitles
Keywords: Animated films; Fantasy films; Science fiction films